2016
DOI: 10.5152/balkanmedj.2015.15975
|View full text |Cite
|
Sign up to set email alerts
|

ST-Segment Elevation in the Right Precordial Leads in Patients with Acute Anterior Myocardial Infarction

Abstract: Background: Elevation of ST segment in leads V3R/ V4R, which is commonly encountered in right ventricular myocardial infarction, may also occur in patients with anterior ST elevation myocardial infarction (STEMI). However, the clinical impact of this finding in the setting of anterior myocardial infarction is not well understood. Aims: We aimed to investigate the prognostic value of ST segment elevation in leads V3R/V4R in patients with first acute anterior myocardial infarction. Study Design: Prospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Furthermore, we observed that the patients with late STE in V 4 R had higher SYNTAX score compared to other two groups. On the contrary, Pourafkari et al investigated the prognostic value of STE in lead V 4 R in patients with anterior STEMI and they concluded that it does not seem to predict the prognosis (Pourafkari et al, 2016). However, they found that patients with STE in lead V 4 R had lower LVEF, their study population is relatively small to reach to statistical significance.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, we observed that the patients with late STE in V 4 R had higher SYNTAX score compared to other two groups. On the contrary, Pourafkari et al investigated the prognostic value of STE in lead V 4 R in patients with anterior STEMI and they concluded that it does not seem to predict the prognosis (Pourafkari et al, 2016). However, they found that patients with STE in lead V 4 R had lower LVEF, their study population is relatively small to reach to statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…There are several studies reported a relatively high incidence of concurrent right precordial STE in patients with anterior STEMI (Barsheshet et al, 2011;Pourafkari et al, 2016;Tusun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STE in lead V4R can indicate right ventricular infarction in patients with inferior infarction, which is associated with a poor prognosis and can lead to arrhythmias and conduction disorders and VF. 1 - 3 Limited data indicated that STE in lead V4R in patients with anterior infarction is associated with a poor prognosis. 4 …”
Section: Introductionmentioning
confidence: 99%